THE IMPACT OF SOCIAL RELATIONS IN THE FAMILY ON THE BEHAVIOR OF CHILDREN - Turdiyeva Nigora (Journals Park Publishing, 2022)
Our people have been paying special attention to the relations of brothers and sisters in the post-parental and post-child relations from the distant past. The presence and preservation of warm relations between children in the family, the status of children in the family are reflected in the oral creativity samples of the people of munsabat. This is exactly what the article says about sibling relationships in the family.
Keywords: sibling munosabat; aka-uka; oila